Comparison of organ dysfunction patterns in pediatric hemophagocytic lymphohistiocytosis and sepsis: incidence, adverse outcomes, and cluster characteristics - Gan, Jinpeng; Li, Xun; Yan, Haipeng; Li, Xiao; Wang, Xiangyu; Xie, Longlong; Luo, Ting; Yang, Yufan; Yang, Haixia; Luo, Haiyan; Zhang, Xinping; Huang, Jiaotian; et al. (Frontiers in Pediatrics, 2025)
BackgroundHemophagocytic lymphohistiocytosis (HLH) and severe sepsis share similarities in their clinical manifestations, and both have high risks of developing multiple organ dysfunction syndrome (MODS). The aim of this study was to investigate the similarities and differences in organ dysfunction patterns among pediatric patients with HLH and severe sepsis.MethodsPediatric patients diagnosed with either HLH or severe sepsis from a tertiary children's hospital over a 5-year period were included. Eleven complications representing organ dysfunction in major systems (hepatic, cardiovascular, respiratory, renal, hematologic, neurologic, and gastrointestinal) were examined. The primary outcome was adverse outcome, defined as in-hospital death or discharge following withdrawal of advanced life-sustaining treatment. The incidence and adverse outcome rates of organ dysfunction among pediatric patients with HLH and severe sepsis were compared, along with the cumulated number of complications and the correlation networks of complications, as well as laboratory characteristics.ResultsThis study included 231 pediatric patients with HLH and 259 with severe sepsis. Adverse outcomes occurred in 15.2% of HLH patients and 18.9% of severe sepsis patients. In HLH, the most prevalent complications were hepatic injury (46.8%) and coagulopathy (43.3%), while adverse outcome rates were highest among patients who developed ARDS (81.8%) and heart failure (77.8%). In severe sepsis, the leading complications were shock (69.9%), respiratory failure (52.1%), and coagulopathy (51.0%); adverse outcome rates were highest among patients with heart failure (67.5%), hepatic failure (61.9%), and ARDS (50%). For most complications investigated, HLH showed lower incidences compared to severe sepsis, but with similar or higher adverse outcome rates. Under the same number of complications, HLH had a higher adverse outcome rates than severe sepsis. However, patients with severe sepsis tended to develop more complications (median 3 vs. 2, P < 0.0001), resulting in similar overall adverse outcome rates for these two conditions.ConclusionsThe incidence, adverse outcome rates, and clustering patterns of organ dysfunction differed between HLH and severe sepsis. Strategies to improve prognosis should vary for each condition. In HLH, preventing the development of severe organ dysfunction is crucial, whereas in severe sepsis, the emphasis should be on preventing the clustering of multiple complications.